Decoupling Control - Wang, Qing-Guo (Springer Berlin Heidelberg, 2003)
Decoupling or non-interactive control has attracted considerable research attention since the 1960s when control engineers started to deal with multivariable systems. The theory and design techniques for decoupling control have now, more or less matured for linear time-invariant systems, yet there is no single book which focuses on such an important topic. The present monograph fills this gap by presenting a fairly comprehensive and detailed treatment of decoupling theory and relevant design methods. Decoupling control under the framework of polynomial transfer function and frequency response settings, is included as well as the disturbance decoupling problem. The emphasis here is on special or relatively new compensation schemes such as (true and virtual) feedforward control and disturbance observers, rather than use of feedback control alone. The results are presented in a self-contained way and only the knowledge of basic linear systems theory is assumed of the reader
Keywords: Engineering; Control, Robotics, Mechatronics; Vibration, Dynamical Systems, Control; Systems Theory, Control; Statistical Physics, Dynamical Systems and Complexity; System theory; Statistical physics; Dynamical systems; Vibration; Dynamics; Control engineering; Robotics; Mechatronics; Störgrößenaufschaltung; Entkopplung; Lineares dynamisches System; Mehrgrößenregelungssystem; Reglerentwurf